Autonomic responses to facial expression tasks in children with autism spectrum disorders: Cross-section study - Gonzaga, Caroline Nunes [UNESP]; Valente, Heloisa Balotari [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Laurino, Maria Júlia Lopez [UNESP]; Santos, Lorena Altafin [UNESP]; Stoco-Oliveira, Mileide Cristina [UNESP]; Rodrigues, Mariana Viana [UNESP]; Ribeiro, Armênio Alcântara [UNESP]; Bofi, Tânia Cristina [UNESP]; de Carvalho, Augusto Cesinando [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Elsevier, 2021)
Background: The autonomic nervous system has an influence on emotions and behavior modulation, however, the relationship between autonomic modulation impairment and the autism spectrum disorder (ASD) is yet to be fully described. Aims: To evaluate the autonomic responses of children with and without ASD through the non-linear, and linear heart rate variability (HRV) measures, and assess the correlation between these responses, the severity and behavioral symptoms of autism. Methods and procedures: 27 children diagnosed with ASD (EG = experimental group) and 28 matching controls (CG = control group) were evaluated. The HRV was evaluated in 15 min sections at the following moments: I) Resting condition; II) During facial expression tasks; and III) Recovery. The severity and behavioral symptoms of autism were evaluated by the Childhood Autism Rating Scale (CARS) and Autistic Behaviors Checklist (ABC) scales. Outcomes and results: The facial expression tasks influenced the activity of the autonomic nervous system in both groups, however the EG experienced more autonomic changes. These changes were mostly evidenced by the non-linear indices. Also, the CARS and ABC scales showed significant correlations with HRV indices. Conclusions and implications: Children with ASD presented an autonomic modulation impairment, mostly identified by the non-linear indices of HRV. Also, this autonomic impairment is associated with the severity and behavioral symptoms of autism.
Keywords: Autism spectrum disorders; Autonomic nervous system; Facial recognition; Non-linear dynamic